Dielectric behaviours of peo-licf 3 so 3 electrolytes / Siti Zaubidah Abdullah - Siti Zaubidah, Abdullah (Universiti Teknologi MARA, Negeri Sembilan, 2013)
Polymer electrolyte composed of poly (ethylene oxide) as a host polymer and LiCF 3 SO 3 as salt was studied. Different compositions of PEO-LiCF 3 SO 3 electrolytes were prepared by solution casting technique. Measurement of conductivity and dielectric properties were carried out on these films as a function of frequency at various temperatures. The highest conductivity obtained was 7.75 x 10 -8 S/cm for a ratio of 80 wt% PEO: 20 wt% LiCF 3 SO 3 . The relaxation time, τ for the ionic charge carriers, was obtained from the variation of loss tangent (tan δ) with frequency for the highest conductivity value. The linear behavior of temperature dependence of the complex film appears to obey the Arrhenius Law. The activation energy for the highest conductivity PEO-LiCF 3 SO 3 sample was found 0.74 eV.